2022
DOI: 10.1044/2021_ajslp-21-00145
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions for Dysphagia in Parkinson Disease: A Systematic Review

Abstract: Purpose: Dysphagia is a common sequela of Parkinson disease (PD) and is associated with malnutrition, aspiration pneumonia, and mortality. This review article synthesized evidence regarding the effectiveness of interventions for dysphagia in PD. Method: Electronic searches were conducted in Ovid MEDLINE, Embase, Cochrane Central Register of Controlled Trials, CINAHL, and speechBITE. Of the 2,015 articles identified, 26 met eligibility criteria: interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…Data regarding whether dopaminergic PD medications can improve dysphagia are equivocal ( Gandhi and Steele, 2022 ). It has been suggested for many years that swallowing dysfunction is not solely related to nigrostriatal dopamine deficiency and may have a non-dopaminergic influence ( Hunter et al, 1997 ), which may explain the observed lack of response to dopaminergic medications in some cases.…”
Section: Dysphagia In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding whether dopaminergic PD medications can improve dysphagia are equivocal ( Gandhi and Steele, 2022 ). It has been suggested for many years that swallowing dysfunction is not solely related to nigrostriatal dopamine deficiency and may have a non-dopaminergic influence ( Hunter et al, 1997 ), which may explain the observed lack of response to dopaminergic medications in some cases.…”
Section: Dysphagia In Parkinson’s Diseasementioning
confidence: 99%
“…It has been suggested for many years that swallowing dysfunction is not solely related to nigrostriatal dopamine deficiency and may have a non-dopaminergic influence ( Hunter et al, 1997 ), which may explain the observed lack of response to dopaminergic medications in some cases. A systematic review of interventions for dysphagia identified nine studies that had evaluated the efficacy of different dopaminergic medications (levodopa, carbidopa, apomorphine, domperidone, and rotigotine) with mixed results ( Gandhi and Steele, 2022 ). A study undertaken in 15 patients with advanced PD whose motor symptoms were responsive to levodopa only found clinically relevant, objective improvement of dysphagia after oral administration of levodopa and evaluation using FEES in about 50% of subjects ( Warnecke et al, 2016 ).…”
Section: Dysphagia In Parkinson’s Diseasementioning
confidence: 99%
“…Recent meta-analysis demonstrated the efficacy of the Lee Silverman Voice Treatment in increasing vocal loudness and functional communication among individuals with PD 69 . Speech language therapy (SLT) has potential benefits for PD dysphagia 70 . Intensive SLT is effective for hypophonia and can lead to some improvement of voice pitch but behavioral speech rehabilitation in PD still needs validation 71 .…”
Section: Parkinson Disease Rehabilitationmentioning
confidence: 99%
“…7 Furthermore, synthesising and comparing study results to direct treatment for people with OD in PD is necessary. Two recently published systematic reviews by Gandhi and Steele 8 and López-Liria et al 9 concluded that there is an ongoing significant…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, synthesising and comparing study results to direct treatment for people with OD in PD is necessary. Two recently published systematic reviews by Gandhi and Steele 8 and López-Liria et al 9 concluded that there is an ongoing significant lack of fundamental scientific evidence on the treatment of OD in PD. In an attempt to address this issue, Schindler et al 10 established a consensus on the treatment of OD in PD.…”
Section: Introductionmentioning
confidence: 99%